KAJIAN KEPUASAN MAHASISWA TERHADAP KUALITAS PELAYANAN DI LINGKUNGAN UNIVERSITAS SAMUDRA - Dhian Rosalina; Muhammad Rizqi Zati; Dyah Ayu Ardiyanti (Universitas Medan Area, 2016)
The quality of academic services is a comparison between the perceived academic service customers or stakeholders with the quality of academic services that diharapkanpelanggan. The purpose of this study was to determine how the level of student satisfaction on the performance of academic services at the University of the ocean, and identify as to whether the expectations of students as users of our services to academic services at the University of the ocean.The population in this study were all students of both the semester active maaupun aajaraan odd year 2016-2017 as users of services from academic services, which the respondents of this activity drawn from five faculties at the University of the ocean environment. Side technique used is proportional stratified random sampling which classifies the populationconsists of five faculties. The method used is the gap analysis that compares the perceptions of respondents mahasiswaa expectations with reality.From the results of the study shows that, for services such as facilities and media university lectures and attitude of staff behavior akademikberdasarkan student perceptions require improved performance. While factors - other factors such as library facilities, attitudes and behavior of faculty, administrative staff and library responsiveness, competence of lecturers and administrative staff, is perceived quite well by studentsKeywords : service quality, Gap Analysis